The Influence of Transformational Leadership and Social Interaction on Employee Performance with Work Motivation as Mediating Variable - M. Mahmud; Jannati Tangngisalu; Edy Jumady (Manunggal Halim Jaya, 2025)
This study aims to analyze the influence of leadership and social interaction on employee performance, with work motivation serving as a mediating variable, at the South Makassar Primary Tax Office. The background of this research is based on the phenomenon of low employee performance, which is influenced not only by leadership factors but also by social interactions among employees and the motivation they possess. The research employed a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM) as the analysis technique. Data were collected through questionnaires distributed to employees of the South Makassar Primary Tax Office, who served as the research respondents. The results of the study indicate that: (1) leadership has a negative and insignificant effect on employee performance; (2) social interaction has a positive and significant effect on employee performance; (3) work motivation has a positive and significant effect on employee performance; (4) leadership has a positive and significant effect on work motivation; (5) social interaction has a positive and significant effect on work motivation; (6) leadership has a positive and significant effect on employee performance through work motivation; and (7) social interaction has a positive and significant effect on employee performance through work motivation. The conclusion of this study is that work motivation serves as a key mediating variable, bridging the influence of leadership and social interaction on employee performance. Therefore, improving employee performance can be achieved by strengthening work motivation through inspirational leadership and harmonious social interaction within the organization.